On the relation between government expenditure and revenue in South Africa: An empirical investigation in a nonlinear framework - Kazeem Abimbola Sanusi (Cogent Economics & Finance, 2020)
The study explores the nonlinear linkage between government expenditure and government revenue using quarterly data from the first quarter of 1965 to the second quarter of 2019. Linear models are first deployed to determine the order of integration of the variables, cointegration, granger causality and variance decomposition within the SVAR model. Nonlinear techniques are employed to spot the asymmetric relation of the univariate and the expenditure and revenue linkage. Asymmetric adjustments are carried out to unknot the dynamic mechanism based on the threshold vector autoregressive model (TVAR) and threshold vector error-correction model (TVECM). Finally, the Markov Switching model is employed to determine the tendency of the variables to remain in a particular region and their transition probabilities. The empirical findings suggest the presence of nonlinear but one-way causal relation between government expenditure and revenue. The results show that adjustment mechanism of government expenditure towards the equilibrium is more persistent than government revenue when the threshold level is attained.
Keywords: E60; E62; Q02; 330; expenditure; nonlinearity; revenue